Information Trends in South Africa with Specific Reference to the Development of an Information Policy for the Electronic Media - Nina Overton (Communicare)
The Information society in South Africa seems to be much more complex and much less predictable than those in most other countries. In many respects it is a First World country in terms of technology, sophisticat- ed media and computerisation. From that viewpoint, it faces the same kind of complex- ities than any other technological society. On the other hand, it is also a Third World coun- try and an integral part of Africa: from that viewpoint it also has to face a different kind of complexity, namely that of languages, cul- tures, life-styles etc. This makes it difficult to assess and anticipate the effects of global in- formation trends such as information over- load, allenation and resistance, the informa- tion paradox and the Information elite. In planning an information strategy for the country, it seems that thorough analysis of the different audiences and their information needs, accompanied by a careful segmenta- tion strategy, is a very high priority. Deregu- lation and privatisation of the electronic me- dia are also advocated, despite financial difficulties and the risk of information over- load. This will call for a greater responsibili- ty and gatekeeping function on the part of communication practitioners in South Africa. Possible options regarding a deregulation policy for the electronic media in South Africa are also explored.